Blood lead level in children with neurologic disorders: a case- control study. - parhoudeh, Marzieh; inaloo, Soroor; zahmatkeshan, Mozhgan; seratishirazi, zahra; Haghbin, Saeedeh (Iranian Journal of Child Neurology, 2018)
Aim: To investigate blood lead level (BLL) in children with neurologic disorders of unknown causes and compare with normal children. Methods: In this prospective case control study, 68 patients aged 1 to 18 years with neurologic disorders of unknown causes, were selected during a 12 month period from Sep. 2013. They were compared with 1:1 ratio, age and sex matched healthy children. BLL was checked from all participants using 3 cc heparinized venous blood sample. Level of ≥5 mcg/dl was considered toxic dose. Results: Totally, 136 children (68 cases and 68 controls) with mean ages of 5.20±4.12 and 4.18±3.86, respectively, entered the study. Mean BLL was higher in case group than in controls but the difference was not significant (P=0.84), though they were less than toxic levels in both. Also, the difference in mean BLLs were not significant in terms of living place, sex and age. Totally, 17.7% 0f the study sample had BLL ≥5 mcg/dl. The frequency of BLL ≥5 mcg/dl was significantly higher in case group (P=0.024) with and odds ratio 2.9 times higher (95% CI: 1.066-7.60). Conclusions: Strategies in public health must focus on practicing primary and secondary preventions of lead exposure in children.